ANALISIS STRATEGI PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DALAM UPAYA PENGENTASAN KEMISKINAN DI KECAMATAN NUSA PENIDA - Mustika, Made Dwi Setyadhi (Buletin Studi Ekonomi; VOL.18.NO.2.AGUSTUS 2013. (PP 85-190), 2014)
Abstract: Analysis of Quality Improvement Strategies of Human Resources as the Effort of Poverty Reduction in the District of Nusa Penida. This study discusses about the strategy for improving the quality of human resources in Klungkung regency, which is focused in the village of Nusa Penida Batukandik. The analysis used is qualitative descriptive analysis and SWOT analysis. Analytical results from this study can be described as follows: (1) analysis of the indicator variable quality of human resources (HR) provides results of several indicators that are analyzed, showing the quality of human resources related to living conditions itself, and (2) SWOT analysis carried out showed that the results of the village Batukandik have different strengths that can be utilized in an effort to alleviate poverty. But keep in mind a fundamental weakness, namely the availability of clean water is very limited, and a low sense of optimism and initiative of rural communities to improve quality of life.
Keywords: Quality of human resources, Poverty, SWOT